Роль крымского микока в поисках генетической подосновы костенковско-стрелецкой культуры - Чабай, В.П. (Археологический альманах, 2009)
This paper is analyzing the well known hypothesis about the origin of Early Upper Palaeolithic Streletskaya industry.